Islamic perspective of Sociology and Anthropology: some reflections - Md. Noon, Hazizan (International Institute of Islamic Thought and International Islamic University Malaysia, 2017)
This edited book is intended to provide Islamic inputs on important topics in the study of sociology and anthropology. Generally, the work consists of selected but important topics for sociological and anthropological knowledge. Each topic includes some basic ideas about it with some necessary elaboration, examples and illustrations. The main highlight is the authors’ attempts to relate the topic to Islam in one way or the other in their own ways. Since each chapter is written by different author/s, it should be expected that the perspective of each respective writer is understandably inclined towards his/her approach, preference and style. This is due partly to their different academic background, thinking orientation, interest and approach. Despite the apparent differences at the secondary and other lower levels, one should notice the overall outlook of all writings which reveal their commonality and this reasonably forms the running theme of the work. This also implies that the diversity in individuals’ perceptions is ultimately unified by their common Islamic principles and values that form the core of Islamic perspective. This book is meant for all categories of readers. Its general purpose is for the readers to gain an overview of the core themes in the study of sociology and anthropology while at the same time be exposed to the initial Islamic insights and perspective/s as seen by different authors.